Methyl to trifluoromethyl substitution as a strategy to increase the membrane permeability of short peptides. Issue 43 (22nd October 2021) - Ono, Takahiro; Aikawa, Kohsuke; Okazoe, Takashi; Morimoto, Jumpei; Sando, Shinsuke
Abstract : CH3 to CF3 substitution on a side chain of proteiogenic amino acids increases the membrane permeability of peptides. Abstract : Here, we investigated the effect of CH3 to CF3 substitution on the membrane permeability of peptides. We synthesized a series of peptides with CF3 groups and corresponding nonfluorinated peptides and measured the membrane permeability of the peptides. As a result, we demonstrated that CH3 to CF3 substitution is useful for increasing the membrane permeability of di-/tri-peptides.